LC-MS characterization of valsartan degradation products and comparison with LC-PDA - Sumaia Araújo Pires; Letícia Martins Mota; Jerusa Simone Garcia; Phellipe Honorio Amaral; Eduardo César Meurer; Marcos Nogueira Eberlin; Marcello Garcia Trevisan (Universidade de São Paulo, 2015)
abstract Valsartan was submitted to forced degradation under acid hydrolysis condition as prescribed by the ICH. Degraded sample aliquots were separated via HPLC using a Hypersil ODS (C18) column (250 x 4.6 mm i.d., 5 µm). Either photodiode array (PDA) detection or mass spectrometry (MS) full scan monitoring of HPLC runs were used. HPLC-PDA failed to indicate Valsartan degradation under forced acid degradation, showing an insignificant peak area variation and that Valsartan apparently remained pure. HPLC-MS using electrospray ionization (ESI) and total ionic current (TIC) monitoring did not reveal any peak variation either, but inspection of the ESI mass spectra showed the appearance of m/z 306 and m/z 352 ions for the same retention time as that of Valsartan (m/z 436). These ions were identified as being protonated molecules of two co-eluting degradation products formed by hydrolysis. These assignments were confirmed by ESI-MS/MS with direct infusion of the degraded samples. The results showed that the use of selective HPLC-MS is essential for monitoring Valsartan degradation. Efficient HPLC separation coupled to selective and structural diagnostic MS monitoring seems therefore mandatory for comprehensive drug degradation studies, particularly for new drugs and formulations, and for method development.